2022
DOI: 10.1093/ejcts/ezac375
|View full text |Cite
|
Sign up to set email alerts
|

Early- and mid-term outcomes following redo surgical aortic valve replacement in patients with previous transcatheter aortic valve implantation

Abstract: Objectives To analyze the early and mid-term outcomes after redo surgical aortic valve replacement (SAVR) in patients with previous transcatheter aortic valve implantation (TAVI). Methods Retrospective single-center analysis of early and mid-term outcomes following redo SAVR in patients with previous TAVI between 2013 and 2020. Primary outcomes were in-hospital mortality and mid-term survival. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 19 publications
0
11
0
Order By: Relevance
“…The STS-PROM reported in the literature ranges from 4.8% to 11.6% (Table 1), with Yokoyama and colleagues reporting an average of 8.1% in their meta-analysis [9]. The median time between TAVR and operative management reported by Yokoyama and colleagues was 9.4 months [9], which is slightly longer than in our experience (7 months) [16]. The average time from TAVR to operative intervention reported in the literature ranges from 2.5 to 27.6 months (Table 1).…”
Section: Patient Profile and Indicationsmentioning
confidence: 48%
See 3 more Smart Citations
“…The STS-PROM reported in the literature ranges from 4.8% to 11.6% (Table 1), with Yokoyama and colleagues reporting an average of 8.1% in their meta-analysis [9]. The median time between TAVR and operative management reported by Yokoyama and colleagues was 9.4 months [9], which is slightly longer than in our experience (7 months) [16]. The average time from TAVR to operative intervention reported in the literature ranges from 2.5 to 27.6 months (Table 1).…”
Section: Patient Profile and Indicationsmentioning
confidence: 48%
“…In our experience, these most commonly include aortic surgery (i.e. root repair and/or ascending aorta repair), mitral valve repair, and coronary artery bypass grafting (CABG) [16]. Yokoyama et al [9] also reported that aortic surgery was the most common concomitant procedure, followed by mitral valve repair/replacement and CABG.…”
Section: Patient Profile and Indicationsmentioning
confidence: 98%
See 2 more Smart Citations
“…The largest so far observational analysis with 5,756 patients with previous TAVI, the incidence of redo SAVR after TAVI was 0.5% with the most frequent indication being infectious endocarditis (67.8% of patients). For most patients, 60.7% required additional cardiac surgical procedures and the overall 12-month mortality was 33.5% ( 42 ). On the other hand, ViV TAVI is associated with several considerations, including the risk of coronary obstruction, prosthesis-patient mismatch, and the need for previous surgical bioprosthesis cracking.…”
Section: Current Transcatheter Valve Devices: Lifetime Management And...mentioning
confidence: 99%